2005
DOI: 10.1097/01.gme.0000184425.73567.12
|View full text |Cite
|
Sign up to set email alerts
|

Oral hormone therapy with 17??-estradiol and 17??-estradiol in combination with norethindrone acetate in the prevention of bone loss in early postmenopausal women: dose-dependent effects

Abstract: There is a dose-dependent effect of E(2) on BMD. The addition of NETA seems to enhance the response in BMD observed with E(2). Low doses of E(2) (1 mg and lower) can be considered for the prevention of osteoporosis, while titrating the hormone dose to individual patient's needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 37 publications
0
24
0
6
Order By: Relevance
“…Использование самой низкой клинически эффектив-ной дозы -ключевое положение при любых заболевани-ях -приобретает особую важность в случае МГТ, посколь-ку она назначается для лечения вазомоторных симпто-мов у женщин старшего возраста и не по жизненно важ-ным показаниям [21].…”
Section: ключевые словаunclassified
“…Использование самой низкой клинически эффектив-ной дозы -ключевое положение при любых заболевани-ях -приобретает особую важность в случае МГТ, посколь-ку она назначается для лечения вазомоторных симпто-мов у женщин старшего возраста и не по жизненно важ-ным показаниям [21].…”
Section: ключевые словаunclassified
“…erhöht ( Tab. 5 ) [26,30,31] . Allerdings liegt die Versagerrate relativ hoch: unter der oralen Dosis von 0,25 mg Östradiol wurde nach 2 Jahren ein Knochenmasseverlust von 1 2% bei 20% der Patientinnen festgestellt [30] .…”
Section: Addendum 2: Niedrig Dosierte Hormonersatztherapieunclassified
“…5 ) [26,30,31] . Allerdings liegt die Versagerrate relativ hoch: unter der oralen Dosis von 0,25 mg Östradiol wurde nach 2 Jahren ein Knochenmasseverlust von 1 2% bei 20% der Patientinnen festgestellt [30] . Keine Zunahme der Knochendichte wurde unter einer 2-jährigen transdermalen Therapie mit 25 g Östradiol bei 40,4%, mit 50 g bei 20,7% und mit 75 g bei 16,1% der Frauen festgestellt [31] [30] .…”
Section: Addendum 2: Niedrig Dosierte Hormonersatztherapieunclassified
See 1 more Smart Citation
“…This preventive effect is maintained: the PERF study [5] demonstrated that administration of hormone therapy in early post-menopause offers a long-lasting benefit for the prevention of postmenopausal bone loss and osteoporotic fracture. Lower doses than previously thought necessary are now proving effective [2,[6][7][8], and a very low dose estrogen product has recently been licensed for osteoporosis prevention by the US Food and Drugs Administration.…”
Section: Hormone Replacement Therapymentioning
confidence: 99%